Hedonist in The Hungarian Gulag: György Faludy’s Memoir Prose - Pálfalvi, Lajos (Porównania, 2024)
György Faludy (1910–2006) became popular in the 1930s with his reworkings of Villon’s ballads. However, this success did not win over critics, who continue to struggle in placing him within the history of Hungarian literature. He belonged to the non-communist left, was an oppositionist, and was in trouble with the censors. In 1938 he left for Paris, and later fled to Morocco to escape the German occupation. He served in the United States military and returned to Hungary after the war. Arrested in 1950, then interned in the cruelest forced labour camp. Following the Soviet invasion in 1956, he wrote a memoir entitled My Happy Days in Hell. This memoir deviates considerably from traditional martyrdom narratives; it is more akin to a picaresque novel, as the protagonist experiences extraordinary adventures in the cruel and grotesque world of communism. The author never lost his sense of humour even in the Hungarian Gulag, when he was close to death.